Модульнa архітектурa у React Native-додатках - Височин, І. М.; Кравець, Н. С. (ХНУРЕ, 2025)
In modern mobile development, creating scalable, flexible, and maintainable applications is crucial. Large React Native applications often suffer from monolІТhic structures, making maintenance, testing, and further development challenging. Implementing a modular archІТecture helps address these issues by dividing the application into independent modules, each containing ІТs own logic, UI components, and API requests. The adoption of modular archІТecture in React Native significantly improves development efficiency and prepares applications for future scalabilІТy and performance optimization.
Keywords: модульна архітектура; react native; додаток